TELAAH TEKNIK DAN BENTUK PENILAIAN ASPEK PENGETAHUAN SERTA KETERAMPILAN DALAM BUKU TEKS SISWA BAHASA INDONESIA KELAS VII KURIKULUM 2013 - Anita Hidayah; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2019)
This research has purposed to describe (1) assessment technique of knowledge aspects, (2) assessment technique of skill aspects, and also (3) assessment form of knowledge aspects that be found in student’s textbook of VII class Indonesian language Curriculum 2013. This study is descriptive qualitative research. The data and data source of study are words, phrases, sentences, paragraphs, and discourses which contain technique and form of assessment of knowledge and skill aspects. The result shows that both techniques of assessment of knowledge and skill aspects and assessment form of knowledge aspect haven’t loaded yet entirely in student's student’s textbook of VII class Indonesian language Curriculum 2013